The Urgency of Implementing the Police Professional Code of Ethics Based on the Indonesian National Police Regulation Number 7 of 2022 in Addressing Abuse of Authority and Increasing Public Trust in the Police Institution - Erikha, Annisa; Sara, Rineke (Indonesian Journal of Multidisciplinary Science, 2025)
Based on Indonesian National Police Regulation Number 7 of 2022, this study attempts to examine police personnel' accountability in cases of transgressions of the Police Professional Code of Ethics. The study highlights the urgency of implementing the code of ethics as an instrument for supervising and controlling the behavior of police officers in order to maintain professionalism, integrity, and public trust in the police institution. This study employs a normative legal approach as its methodology, examining case studies and laws pertaining to ethical transgressions by police. The findings show that the application of the code of ethics, which incorporates elements of personal, social, institutional, and state ethics, has provided a clearer legal framework in enforcing moral and professional standards for police officers. However, challenges still exist in its implementation, including a lack of transparency in the enforcement process and ongoing cases of abuse of power that tarnish the police's image. Therefore, there is a need to strengthen the supervision mechanisms, increase accountability through the Police Code of Ethics Commission (KKEP), and optimize sanctions that are educational and have a deterrent effect on violators. The main conclusion of this study is that the success of enforcing the police professional code of ethics greatly depends on the effectiveness of regulations, consistency in the application of sanctions, and the involvement of the public in overseeing police performance to ensure that every police officer performs their duties with the highest regard for legal values, justice, and human rights.